Ms. Idiomatic Expressions Found in Arctic Monkeys’ Song “Do I Wanna Know?” - Nita, Sri; Otong Setiawan Djauhari (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The present study aims to identify and analyze idiomatic expressions in the lyrics of “Do I Wanna Know?” by Arctic Monkeys. Idioms are non-literal expressions that often cause difficulty for English learners due to their figurative nature. This study employs a descriptive qualitative approach with a focus on semantic and contextual analysis based on the theories of Palmer (2007), Larson (2010), and Halliday (2014). The results indicate that the song contains several idiomatic expressions that reflect emotional states such as longing, regret, and insecurity. These findings suggest that song lyrics can serve as effective, authentic, and engaging media for learning idioms in EFL contexts. The study also highlights the pedagogical and cultural implications of using popular songs as teaching materials.